OPTIMIZATION OF PROJECT TIME AND COST IN PANDEMIC ERA BY TIME COST TRADE OFF METHOD OF UNIVERSITAS NEGERI MEDAN CASE STUDY - Gea Geby Aurora Syafridon; Syahrizal; Rahmi Karolina; Muhammad Agung Putra Handana; Maria Christin (Jurusan Teknik Sipil, Politeknik Negeri Medan, 2022)
The quality of project construction is constrained by the triangle model of project management, refers to the boundaries of scope, cost and time. The construction project at Universitas Negeri Medan is one of the projects that is experiencing delays and does not meet one of the limitations of triple constraints that must be met by each project. This study has aims to identify the acceleration of project duration using the Time Cost Trade Off method with alternative additions of working hours (overtime) 1 hour, 2 hours, and 3 hours as well as the addition of the number of workers by 10%, 15%, 20%, and 25% from the beginning. From the results of the analysis using this method, it was concluded that the addition of the number of workers as much as 10% from the original is more profitable, where the optimum time of acceleration of the project duration is for 171 calendar days and the optimum cost resulting from the acceleration of the project duration is Rp. 14,059,057,900.00.